Fundamentals of Thermal and Nuclear Power Generation - Koizumi, Yasuo, editor 635907; Okawa, Tomio, editor 635908; Mori, Shoji, editor 635910 (Oxford, UK : Elsevier, 2021)
Fundamentals of Thermal and Nuclear Power Generation is the first volume in the JSME Series in Thermal and Nuclear Power Generation. The first part of this volume provides a thorough and complete reference on the history of thermal and nuclear power generation, which has informed and sculpted today’s industry. It prepares readers for subsequent publications in the series that address more advanced topics and will particularly benefit early career researchers and those approaching the industry from an alternative discipline. Modern thermal and nuclear power generation systems and technologies are then explored, including clear analysis on the fundamentals of thermodynamics, hydrodynamics, thermal engineering, combustion engineering, and nuclear physics. The impact of these technologies on society is considered throughout, as well as supply issues, accident risk analysis, and important emission and sustainability considerations.